Attitudes of doctors working in emergency departments in the Gauteng area towards family witnessed resuscitation - Gordon, Evelyn Dawn (My University, 2011)
Resuscitation of patients, be it medical or surgical, occurs on a daily basis in the Emergency Department. The resuscitation is usually pressurised and frantic, as a result family members are escorted out of the resuscitation room to a waiting room where they are isolated from the resuscitation. Since the late 1980’s the practice of Family Witnessed Resuscitation (FWR) has been explored1. FWR means that family members are invited into the resuscitation area whilst the medical team is attempting to resuscitate the patient. This practice has often been suggested but the opinions of medical staff remain varied 2,3,4. Resuscitation as discussed in this report is the medical proceedings that occur at a time when a patient presents with a life threatening emergency, be it medical or surgical, to an emergency department and the medical staff are unsuccessful in re-establishing respiratory efforts and cardiac output to maintain life. A review of the literature indicates that FWR is a means of the family gaining closure when the resuscitation is unsuccessful by observing the process of resuscitation and having their family member’s last moments clearer and more defined in their memory. The decision of FWR is one that needs to be taken by the family after the invitation has been extended by the medical team leader. There needs to be nursing staff available to be in attendance with the family at all times to answer their questions and explain procedures. The views of practitioners surveyed on FWR tend to vary, but irrespective there is a recurrent theme regarding the concerns expressed by emergency room doctors towards FWR. These concerns include traumatisation of the family, increased stress being placed on the medical team to perform while being watched, possible family interference with the resuscitation and the possibility of medico-legal consequences. These concerns are not simply regional but seem to be universal. This study sampled two groups of doctors:  Doctors actively working in emergency departments in the Gauteng area in Medi-Clinic and Life Healthcare facilities. These are private healthcare facilities.  Doctor participants in the University of the Witwatersrand, Faculty of Health Sciences Master in Science in Emergency Medicine programme. These doctors work in emergency departments in both the private and provincial sectors. This study found that there is not complete acceptance of FWR; 48 out of the 101 doctors in the sample had never considered allowing family to witness resuscitation. Doctor’s opinions vary regarding which family members, if any, they would allow to witness resuscitation, at which point in the resuscitation process they would allow family into the resuscitation area and how many family members would be permitted into the resuscitation at any one time. The opinion in this study was that due to space constraints no more than two family members would be allowed in the resuscitation area at any one time. Training and continued professional development seem to impact positively on the practice of FWR. The attendance at American Heart Association (AHA) courses such as Paediatric Advance Life Support (PALS) and AHA Acute Cardiac Life Support (ACLS) positively influences the doctors’ acceptance of FWR. Should death occur due to the acute life threatening emergency and resuscitation attempts are unsuccessful then FWR assists family in coming to terms with the death of a relative and is seen by the public to make the resuscitation a more humane process. The literature review and findings of this study concur that FWR is a practice that should be occurring in emergency departments. Some nursing councils have drawn up guidelines and mission statements that will ensure FWR is common place in the Emergency Departments (Appendix 1). If FWR is to become common practice then emergency departments need to be encouraged to draw up protocols and have processes in place that ensure that this process is performed in a way that allows staff to operate efficiently and the family to gain the most they can from a grave situation. The emergency medicine doctor that is in charge of the patient needs to be aware of the protocols and procedures that are in place in order to be able to facilitate FWR. In studies from KwaZulu Natal5, Western Cape6 and this study from Gauteng show that no unit in South Africa has policies yet. This study found that although FWR is currently not common practice in emergency departments in the Gauteng area, it is a practice that emergency doctors are willing to encourage in the future. The doctor’s attitude toward FWR is influenced positively by attendance at AHA PALS and AHA ACLS courses and the experience of the doctor of working in the emergency department. Doctors do have some concerns about the practice including psychological traumatisation of family members, extended length of resuscitation and medico-legal complications. It was found that parents would be the family members that are most likely to be invited by the medical team to witness the resuscitation of a family member and that the doctor would restrict witnesses to two family members only. It would seem that FWR will start occurring in emergency departments.
MSc (Med), Emergency Medicine, Faculty of Health Sciences, University of the Witwatersrand
Keywords: resuscitation; emergency; family; fanmily witnessed resuscitation